Global Coffea arabica variety trials reveal genotype-by-environment interactions in resistance to coffee leaf rust (Hemileia vastatrix) - Berny Mier y Teran, Jorge C.; Pruvot-Woehl, Solene; Maina, Catherine; Barrera, Santos; Gimase, James Mwita; Banda, Brahim; Meza, Albertino; Kachiguma, Nathan Aliel; Gichuru, Elijah K.; Alvarado, Julio; Kumar, Suresh; Alonso Castillo, Jonny; et al. (Frontiers in Plant Science, 2025)
IntroductionCoffee leaf rust (CLR), caused by the obligate parasitic fungus Hemileia vastatrix, is the most significant constraint in Arabica coffee production worldwide. The disease is ubiquitous, and in severe infections, it can lead to defoliation of coffee plants, impacting yield and quality. The use of resistant varieties is the most cost-effective and sustainable strategy for managing coffee leaf rust. Identifying highly resistant varieties, as well as environments where these varieties perform similarly, is a crucial step in breeding programs.MethodsAn international, multi-institutional effort involved the evaluation of 29 varieties, developed by different breeding programs in coffee-producing countries across the globe, for CLR severity under field conditions at 23 sites in Africa, Asia, and Latin America.ResultsThe results showed that both the genotype and genotype-by-site interaction were highly significant, indicating that resistance to coffee leaf rust depends not only on the genetic makeup but also varies between sites. In general, varieties with interspecific introgressions were more resistant than the nonintrogressed pure Arabicas. Although stability and overall resistance were correlated, some of the most resistant varieties were not the most stable. Four mega-environments were identified, and sites that were better at discriminating for resistance were found across the three continents.DiscussionOverall, this multi-institutional cooperation led to the identification of both locally and globally highly resistant coffee leaf rust varieties, as well as an understanding of their underlying genetics and the further causes of genotype-by-environment interactions concerning coffee leaf rust resistance.